Epilepsy, Vascular Risk Factors, and Cognitive Decline in Older Adults: The Cardiovascular Health Study. (22nd November 2022) - Choi, Hyunmi; Elkind, Mitchell S.V.; Longstreth, W.T.; Boehme, Amelia K.; Hafen, Rebekah; Hoyt, Emma J.; Thacker, Evan L.
Abstract : Background and Objectives: Recent studies have shown that global cognitive ability tends to decline faster over time in older adults (≥65 years) with epilepsy compared with older adults without epilepsy. Scarce data exist about the role of vascular risk factors (VRFs) on cognitive course in epilepsy. We assessed whether the associations of individual VRFs with cognitive trajectory differed depending on the presence of prevalent epilepsy. Methods: The Cardiovascular Health Study is a population-based longitudinal cohort study of 5, 888 US adults aged ≥65 years. Cognitive function was assessed annually with modified Mini-Mental State Examination (3MS; global cognitive ability) and Digit Symbol Substitution Test (DSST; information processing speed). We used linear mixed models to estimate the individual and joint associations of epilepsy and VRFs with cognitive decline by modeling epilepsy × VRF interactions one by one, each adjusted for all other VRFs considered, including demographics, health behaviors, clinical characteristics, and comorbid diagnoses. From these models, we estimated excess mean cognitive decline due to interaction of epilepsy with each VRF. Results: We observed excess mean decline in global cognitive ability (3MS) due to interactions of epilepsy with hypertension (6.6 points greater mean 8-year decline than expected if no interaction; 95% CI 1.3–12.0) and with abstaining from alcohol (5.8 points greater than expected; 95% CI 0.3–11.3). We also observed excess mean decline in information processing speed (DSST) due to interactions of epilepsy with prior stroke (18.1 points greater mean 9-year decline than expected; 95% CI 7.6–28.5), with abstaining from alcohol (6.1 points greater than expected; 95% CI 2.5–9.8), and with higher triglyceride levels (2.4 points greater than expected per SD; 95% CI 0.4–4.3). Discussion: Associations of some VRFs with cognitive decline in older adults are stronger in the presence of epilepsy, suggesting a need for greater attention to vascular protection for preserving brain health in older adults with epilepsy.